A stable multifunctional Zn(Ⅱ) based metal-organic framework for sensitive detection of Hg(II), Cr(VI), nitrobenzene and adsorption of methylene blue. Issue 3 (June 2022) - Li, Jiaxin; Sun, Changyan; Wen, Chaoxia; Wang, Lin; Zhao, Yichen; Li, Wenjun; Chang, Zhidong
Abstract: It is well known that Hg(II) and Cr(VI) are highly toxic, and nitrobenzene and methylene blue (MB) are common organic pollutants. Their detection and removal are still a challenge. Herein, a novel metal-organic framework [Zn(CPA)(DMF)]n has been successfully constructed by the strategy of anchoring Zn 2+ and rigid ligand 2, 5-bis(4′-carboxyphenyl)aniline (H2 CPA). The obtained Zn-MOF has large pores and uncoordinated sites. The structure is stable after immersed in pure water for 30 days and in the pH range of 3–12, which results in good sensing and adsorption potential. Experiments show that this Zn-MOF can be used to detect not only Hg(II) and Cr(VI) with high selectivity and sensitivity in pure water，but also nitrobenzene in DMF. The detection mechanisms are studied in detail. In addition, this Zn-MOF displays good adsorption for methylene blue, and the removal percentage is 92.5%. Graphical Abstract: The Zn-MOF can be used to detect not only Hg(II) and Cr(VI) with high selectivity and sensitivity in pure water，but also nitrobenzene in DMF. In addition, this Zn-MOF displays good adsorption for methylene blue, and the removal percentage is 92.5%. ga1 Highlights: A new synthesized Zn-MOF could be used to detect Hg(II) and Cr(VI) with high selectivity and sensitivity in pure water. The Zn-MOF could be used to detect nitrobenzene in DMF with the detection limit of 2.09 × 10 −5 mol·L −1 . The Zn-MOF displays good adsorption for methylene blue, and the removal percentage is 92.5%.